Genetics of 46, XY gonadal dysgenesis. Issue 1 (January 2022) - Elzaiat, Maëva; McElreavey, Ken; Bashamboo, Anu
Abstract : In 46, XY men, testis is determined by a genetic network(s) that both promotes testis formation and represses ovarian development. Disruption of this process results in a lack of testis-determination and affected individuals present with 46, XY gonadal dysgenesis (GD), a part of the spectrum of Disorders/Differences of Sex Development/Determination (DSD). A minority of all cases of GD are associated with pathogenic variants in key players of testis-determination, SRY, SOX9, MAP3K1 and NR5A1. However, most of the cases remain unexplained. Recently, unbiased exome sequencing approaches have revealed new genes and loci that may cause 46, XY GD. We critically evaluate the evidence to support causality of these factors and describe how functional studies are continuing to improve our understanding of genotype–phenotype relationships in genes that are established causes of GD. As genomic data continues to be generated from DSD cohorts, we propose several recommendations to help interpret the data and establish causality.